Animated Video Media with the Contextual Teaching and Learning (CTL) Learning Model in Mathematics Subjects for Grade IV in Elementary Schools - Ni Putu, Dewi Fitriyanti; I Nyoman Jampel; Desak Putu Parmiti (Journal of Education Technology, 2025)
The utilization of educational facilities and infrastructure in learning remains suboptimal, as they are rarely maximized during the teaching and learning process. This study aims to develop, validate, and evaluate the effectiveness of animated video media based on the Contextual Teaching and Learning (CTL) model for fourth-grade mathematics instruction. This research employs a Research and Development (R&D) design. The research subjects include content experts, instructional design experts, media experts, and students as trial participants. Data were collected through interviews, validation questionnaires, and learning outcome tests. The instruments used consist of interview guides, validation sheets, and test items. Data were analyzed using descriptive quantitative, descriptive qualitative, and inferential statistical methods (t-test). The results indicate that the animated video media is highly valid, with validation scores from content experts (91.5%), instructional design experts (89%), and media experts (93.3%). Individual trials yielded a percentage of 95.15%, small group trials 93.73%, and field trials 93.93%. The media’s effectiveness is demonstrated by the t-test result showing that the tvalue exceeds the critical value (22.483 > 1.670). Therefore, the CTL-based animated video media is proven effective in improving students’ mathematics learning outcomes. These findings suggest positive implications for the development of contextual digital media that enhance meaningful learning experiences.